Early contraceptive implants removal and its associated factors among women using implants at a National Referral Hospital, Kampala Uganda - Gerald Ssebatta; Dan Kabonge Kaye; Scovia Nalugo Mbalinda (BMC, 2021)
Abstract Background Early discontinuation of implant contraceptive methods and reasons for discontinuation remains a major concern for family planning programs. Early discontinuation is related to higher rates of the overall fertility rate, unwanted pregnancies leading to possibly induced abortion. There is paucity of data on the practice of discontinuation of contraceptives in developing countries. The objective of the study was to determine the magnitude of early implants discontinuation among women receiving implants services in the study area and the factors associated with it. Methods A cross-sectional study was conducted from 2nd January to 3rd March 2020. Data were collected from 207 women who had come to remove implants on socio-demographic characteristics, obstetric history, duration of implant, and reasons for wanting to remove the implant. We computed the proportion of those who removed the implant before 18 months (early discontinuation). To assess the factors associated with early discontinuation, we estimated the prevalence ratios with a generalized linear model of the poisson family with a log link and robust error variance. Results The proportion of early implant discontinuation was 87/207(42%). Factor associated with early implant discontinuation included; experience of side effects (PR = 1.1; 95% CI 1.03-1.24; P = 0.001), not having received pre-insertion counseling about the benefits and side effects of contraceptive implants (PR = 1.5; 95% CI 1.02-1.30; P = 0.019) and staying in rural areas (PR = 1.1; 95% CI 1.03-1.27; P = 0.014). Conclusion Nearly one in every two mothers have early discontinuation of contraceptive implants. Factors associated with early implant removal include; experience of side effects, lack of counseling services, and staying in rural areas. There is a need for intervention to address high prevalence of early contraceptive removal through improving on counselling services about possible side effects.